The Pícaro and His Cryptolect (Germanía): Sources in Caló (Para-Romani Andalusian). - Sayers, William (Romance Notes, 2025)
Spanish pícaro is traced via Caló (Andalusian para-Romani) to a Romani root pek - and its several derivatives in the semantic fields of "bake, roast, burn, tease, fornicate, monitor, snoop, steal". The phonological form and these meanings were calqued in the late sixteenth or early seventeenth century onto Andalusian pícar , which already had some comparable literal and figurative meanings. The Caló idiolect displays various forms of wordplay in order to encrypt significations of vital interest to the community. Pícaro is not recorded from fieldwork conducted among los calés , their reticence perhaps founded in a desire to avoid self-incrimination by admitting of a lexeme centered on cunning, deceit, fraud, "cons", and theft. Germanía , often pejoratively called "thieves cant", is similarly traced to Romani notions of encryption rather than to any idea of brotherhood or physical geography.